2020
DOI: 10.31662/jmaj.2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Cardiac Differentiation and Maturation in Pluripotent Stem Cells: A Lesson from Heart Development

Abstract: The heart, one of the more complex organs, is composed from a number of differentiated cells. In general, researchers consider that the cardiac cells are derived from the same origin as mesodermal cells, except neural crest cells. However, as the developmental stages proceed, cardiac mesodermal cells are differentiated into various types of cells via cardiac progenitors and demonstrate different programming in transcriptional network and epigenetic regulation in a spatiotemporal manner. In fact, the metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 69 publications
1
26
1
Order By: Relevance
“…As development proceeds, mitochondria occupy ~20–40% of adult CM volume [ 120 ]. It has been documented that in PSC-CMs, the changes in energy metabolism have important impacts on the ability of CMs to proliferate during early cardiac development, as well as when CMs terminally differentiate during later development [ 121 ]. A previous study reported that an appropriate metabolic shift from aerobic glycolysis to OXPHOS would in turn improve metabolic and functional maturation of human PSC-CMs (hPSC-CMs) [ 122 ].…”
Section: Mitochondrial Biogenesis and Cardiac Maturationmentioning
confidence: 99%
“…As development proceeds, mitochondria occupy ~20–40% of adult CM volume [ 120 ]. It has been documented that in PSC-CMs, the changes in energy metabolism have important impacts on the ability of CMs to proliferate during early cardiac development, as well as when CMs terminally differentiate during later development [ 121 ]. A previous study reported that an appropriate metabolic shift from aerobic glycolysis to OXPHOS would in turn improve metabolic and functional maturation of human PSC-CMs (hPSC-CMs) [ 122 ].…”
Section: Mitochondrial Biogenesis and Cardiac Maturationmentioning
confidence: 99%
“…Glycolysis has been reported to be a major source of energy in mesodermal and cardiac progenitor cells during early cardiac development 10 12 . The oxygen supply to the embryo is limited to diffusion from the placenta until fetal circulation is formed, and thus it is reasonable that glycolysis, which does not require oxygen to produce ATP, plays a central role in energy production in the heart primordium.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen supply to the embryo is limited to diffusion from the placenta until fetal circulation is formed, and thus it is reasonable that glycolysis, which does not require oxygen to produce ATP, plays a central role in energy production in the heart primordium. In contrast, it has been acknowledged that mitochondrial oxidative phosphorylation (OXPHOS), which can produce large amounts of ATP compared with those produced by anerobic glycolysis under the condition of a sufficient supply of oxygen and energy substrates, contributes less to energy metabolism in the embryonic heart than that in the matured heart 10 12 . In fact, cristae density and the number of mitochondria in cardiomyocytes have been reported to be smaller in the embryonic heart than in the matured heart 12 14 , suggesting less reliance on mitochondrial OXPHOS for the production of ATP in cardiac progenitor cells or cardiomyocytes in the embryo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A shift in metabolism is well documented for differentiating stem cells from glycolysis in the pluripotent state to oxidative phosphorylation (OxPhos) [90,91]. Accordingly, S0 and S1 rely on glycolysis and-to a lesser extent-glutamine oxidation for metabolism.…”
Section: Discussionmentioning
confidence: 99%